Analisis pertanggungjawaban penggunaan alokasi dana desa berdasarkan PERPPU No. 1 Tahun 2020 (Studi kasus di Desa Leilem Tiga, Kecamatan Sonder) - Tungka, Isak Brian; Sabijono, Harijanto; Suwetja, I Gede (Yayasan Widyantara Nawasena Raharja, 2024)
This research aims to describe accountability for the use of village fund allocations based on PERPPU Number 1, 2020. The results of the research show that village fund allocation in Leilem village is carried out in four stages, namely the planning stage, implementation stage, monitoring stage, and accountability stage to support community health and welfare. The government provides assistance to support the health and welfare of the community, especially with the COVID-19 virus, there has also been a shift in the budget to the health budget. The government also applies the principles of money for value, accountability and transparency in managing village fund allocations, however there are obstacles in transparency because there is no village website that can make it easier for related parties and the community to access village financial reports or reports on the use of village funds.